The Law Enforcement in Pressing Traffic Accident which Resulting Death - Kadek Oka Suparta; Ira Alia Maerani (Jurnal Daulat Hukum, 2020)
The aim of this studyto know the strategy of law enforcement in suppressing traffic accidents that result in death at the Mojokerto City Police, to find out the factors that support and hinder the Mojokerto City Police in suppressing traffic accidents that result in death, and to find out solutions to obstacles in an effort to suppress traffic accidents resulting in death. The approach method used is juridical normative and juridical socio-logical method, the specifications in the research are descriptive analytical, population and sampling methods are all objects or all symptoms or all events or all units to be studied, data collection techniques use library research and interviews, data analysis used is qualitative. Application of criminal sanctions in cases of traffic accidents and road transportation based on Act No. 22 of 2009 concerning Road Traffic and Transportation. The perpetrator who causes the victim to die is subject to Article 310 paragraph (4) and Article 311 paragraph (1) of Act No. 22 of 2009. In Article 310 paragraph (4) the perpetrator is sentenced to imprisonment of up to 12 (twelve) years or a maximum fine of Rp. 24,000,000.00 (twenty four million rupiah). In Article 311 paragraph (1) the perpetrator is sentenced to imprisonment for a maximum of 1 (one) year or a maximum fine of Rp. 3,000,000.00 (three million rupiah). Factors that influence law enforcement in cases of driver negligence in traffic resulting in death are the legal factors themselves, law enforcement factors, facility factors or facilities that support law enforcement to run smoothly, community factors, namely the environment in which the law applies, cultural factors, criminal and non-penal policy factors. Efforts made by the Traffic Unit against obstacles in an effort to suppress traffic accidents that result in death, are as follows: Preemptive action, Preventive action (prevention), repressive action (repression).